2016
DOI: 10.1002/ecs2.1393
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of natural fungal community assembly during initial decay of coniferous and broadleaf tree logs

Abstract: Abstract. Community assembly processes do not only influence community structure, but can also affect ecosystem processes. To understand the effect of initial community development on ecosystem processes, we studied natural fungal community dynamics during initial wood decay. We hypothesize that fungal community assembly dynamics are driven by strong priority effects of early-arriving species, which lead to predictable successional patterns and wood decay rates. Alternatively, equivalent colonization success o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 40 publications
(67 reference statements)
3
21
0
Order By: Relevance
“…Because of different dependencies and tolerances of microbial taxa on moisture, we expect that microbial communities will shift with spatial location both within stems (Fig. 1: within stem position) (Kubartová et al ., 2012; van der Wal et al ., 2016) and within watersheds (Fig. 1: within watershed position) (Tedersoo et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Because of different dependencies and tolerances of microbial taxa on moisture, we expect that microbial communities will shift with spatial location both within stems (Fig. 1: within stem position) (Kubartová et al ., 2012; van der Wal et al ., 2016) and within watersheds (Fig. 1: within watershed position) (Tedersoo et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Advances in metabarcoding approaches using high‐throughput sequencing (HTS) platforms enable detailed analysis of community composition and have been harnessed to reveal a more complete picture of fungal diversity in a wide range of habitats, including soil and deadwood (Goldmann, Schöning, Buscot, & Wubet, ; Hiscox et al, ; Hoppe et al, ; van der Wal, Klein Gunnewiek, Cornelissen, Crowther, & Boer, ; van der Wal, Ottosson, & Boer, ). Recent studies have demonstrated that diverse taxonomic and ecological functional groups of WIF colonize deadwood (Ottosson et al, ; Purahong et al, ; Song, Kennedy, Liew, & Schilling, ).…”
Section: Introductionmentioning
confidence: 99%
“…Microbial metacommunities are receiving a large amount of recent attention (Fuhrman, ; Fukami et al, ; Hiscox, Savoury, Müller et al, ; Maynard et al, ; Nemergut et al, ; Peay, Bruns, Kennedy, Bergemann, & Garbelotto, ; Prosser et al, ; Van der Wal et al, ), and dispersal is increasingly identified as a key unknown with respect to the maintenance and continuity of these communities in a dynamic landscape (Calhim et al, ; Davison et al, ; Kneitel & Miller, ; Lancaster & Downes, ; Smith, Steidinger, Bruns, & Peay, ). We have demonstrated that fungi can acquire information from the environment, subsequently affecting changes to their allocation strategies to dispersal when faced with competition within the confines of the trade‐off between growth and dispersal.…”
Section: Resultsmentioning
confidence: 99%
“…Access to resources held by other fungi often requires combative antagonism to breach an already occupied space. Variation in competitive ability is common, with distinct hierarchies formed by interactions bound in a substrate (Boddy, ; Stenlid & Gustaffson ; Haňáčková et al, , Van der Wal, Klein Gunnewiek, Cornelissen, Crowther, & Boer, ). Thus, delaying dispersal through delaying reproduction may result in low fitness if a fungal colony cannot withstand the combative assault of a competitively superior fungus.…”
Section: Introductionmentioning
confidence: 99%